What drives the disclosure of corporate philantrophy? An Indonesian context - Rizki Rahma, Kamila; Gusti Anugerah, Eza; Maharani, Bunga (JIFA (Journal of Islamic Finance and Accounting), 2022)
Corporate philantrophy activities have become an important factor for corporate management. Drawing on this issue, this research intends to disclose the effect of profitability, firm size, and audit committee on corporate philanthropy (CSR donations) in manufacturing companies listed on the Indonesia Stock Exchange from 2018 to 2020. The population in this study were manufacturing companies listed on the Indonesian stock exchange. The sample included 352 data sets from 174 companies. Secondary data utilized in this study were derived from the www.idx.co.id. Multiple linear regression for data analysis employed SPSS. This study uncovers that profitability and firm size have a positive effect on corporate philanthropy, while the audit committee has no significant effect on corporate philanthropy. This study provides implications for corporate management that increasing profitability will increase corporate philantrophy.